Ecology of Hydrozetes Berlese, 1902 (Acari, Oribatida) at various water bodies near Bydgoszcz (northern Poland) - Seniczak, Anna (Biological Letters, 2012)
Mites of the genus Hydrozetes Berlese, 1902 are abundant and important in wet habitats and can be useful in palaeoecological studies and bioindication. However, due to problems with their identification, there is still a limited knowledge on their ecology. In this study, 5 Hydrozetes species have been investigated. The most abundant was H. lemnae (about 121 000 ind./m2), which constituted 76% of the total Oribatida at a pond shore in the Botanical Garden in Myślęcinek in Bydgoszcz. Its population density was lower in duckweed and filamentous algae on the water surface of the same pond. This species was found also in several other bodies of water, varying in water quality, but it preferred neutral pH. Hydrozetes thienemanni had a narrower ecological tolerance and was restricted only to a forest pond with neutral pH in Pruszcz, where it dominated among the Oribatida. Three other species - H. lacustris, H. octosetosus, and H. longisetosus - were found only in acid water. The last mentioned species was absent from the peat pond in Bagno Chlebowo Nature Reserve, with a high concentration of sulphur and worse oxygen conditions, but that site was suitable for H. lacustris.